Giardia lamblia Hsp90 pre‐mRNAs undergo self‐splicing to generate mature RNA in an in vitro trans‐splicing reaction. Issue 4 (22nd January 2019) - Iyer, Vinithra; Chettiar, Sivarajan T.; Grover, Manish; Rajyaguru, Purusharth; Nageshan, Rishi Kumar; Tatu, Utpal
Abstract : We have previously shown that the Heat Shock Protein 90 (Hsp90) gene in G. lamblia is expressed from two ORFs localized 777 kb apart. The pre‐mRNAs transcribed from these ORFs are stitched by a trans‐splicing mechanism. Here, we provide mechanistic details of this process by reconstituting the reaction using in vitro synthesized pre‐mRNA substrates. Using RT‐PCR, northern blot and nanostring technology, we demonstrate that the in vitro synthesized pre‐mRNAs have the capability to self‐splice in the absence of nuclear proteins. Inhibition of the trans‐splicing reaction using a ssDNA oligo corresponding to a 26‐nucleotide complementary sequence confirmed their role in juxtapositioning the pre‐mRNA substrates during the self‐splicing reaction. Our study provides the first example of a self catalysed, trans‐splicing reaction in eukaryotes. Abstract :